Treatment of von Willebrand Disease - Curnow, Jennifer; Pasalic, Leonardo; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2016)
Congenital von Willebrand disease (VWD) and acquired von Willebrand syndrome (AVWS) reflect conditions caused by von Willebrand factor (VWF) deficiency and/or defects. VWD is the most common inherited bleeding disorder and AVWS arises from a variety of causes. Since VWF stabilizes and protects factor VIII (FVIII) in the circulation, this is also reduced in many patients with VWD. The treatment of VWD and AVWS therefore primarily entails replacement of VWF, and sometimes FVIII, to protect against bleeding. This may entail the use of VWF concentrates (currently plasma-derived) and/or FVIII concentrates (currently plasma-derived or more increasingly recombinant forms), and/or desmopressin to release endogenous VWF in subgroups of patients. For AVWS additional treatment of the underlying condition is also required. Adjunct therapies include antifibrinolytics. Globally, various formulations exist for both VWF and FVIII concentrates and are differentially available based on manufacturer marketing or regulatory approvals/clearances in different geographies. Also, guidelines for treatment of VWD vary for different localities and recombinant VWF is undergoing clinical trials. The current review provides an overview of the treatment of VWD as currently practiced in developed countries, and also provides a glimpse towards the future.
Keywords: von Willebrand disease; VWD; diagnosis; management; factor concentrates; recombinant VWF; recombinant FVIII